Improving the Ability to Write A Novel Review Using the Reading Guide Method in Class XI MIPA 6 SMA Negeri 1 Nglames, Madiun District, the Academic Year 2022/2023 - Mubarrok, Hafidh; Agustin, Sri; Soleh, Dwi Rohman (International Journal Corner of Educational Research, 2023)
This research is motivated by students' ability to write novel reviews which is still at a low level. From the results of the observation, it is known that the students' results in writing novel reviews have scores below the predetermined passing standards. Then, from the results of the discussion involving various parties, the researcher decided to take a class action research with the title "Improving the Ability to Write Novel Reviews Using the Reading Guide Method in Class XI MIPA 6 SMA Negeri 1 Nglames, Madiun Regency, Academic Year 2022/2023". The method chosen in carrying out this research is a reading guide. This method is a method that involves students being active in compiling a review text. The reading guide method is a method by determining the reading material and then the teacher arranges questions that will be answered by students. The teacher gives several questions that function to obtain the desired results. This research involved 36 students in class XI MIPA 6 at SMA Negeri 1 Nglames. This research uses qualitative descriptive data processing. The discussion is explained and described based on research results and data that has been obtained. Using this method is expected to be a step for students to be able to easily compile reviews.